Towards a sustainable future for ecclesiastical heritage - Henrik Lindblad (Cidades, Comunidades e Território)
Sweden is, according to the World Values Survey, one of the world’s most secularised and modernised countries. In this changing society, the Church of Sweden, until 2000 a part of the State, is responsible for 3,400 well-kept historic church buildings and cemeteries. However, the Church loses more than 80,000 members every year and the active churchgoers as well as the economy is in decline, causing redundant and closed churches. This development is comparable with other countries in Europe, though the Swedish ecclesiastical heritage still enjoys strong legal protection and receives a large annual financial compensation from the State for its conservation.The article shows that the legal and financial framework governing the ecclesiastical heritage is based on a partly outdated expert-oriented and material-based conservation approach with origins in an even older nineteenth-century antiquarian discourse. Instead of supporting the revitalisation of many redundant churches as societal resources, the system encourages well-maintained churches without living use: “zombie-churches”. It is relevant to ask how many of these historic churches can remain accessible to the public in the future? To keep the churches open, can extended or new secular uses, benefitting local communities, be developed and promoted?To achieve desired progress towards a holistic, dynamic and inclusive ecclesiastical heritage, several measures are proposed. My recommendations include identification and synchronisation of heritage discourses in cultural heritage practices and policies, reviewing and updating of the antiquarian system, and strengthening of professional competences in adapted reuse of historic churches as catalysts for sustainable development.